IMPROVING STUDENTS' WRITING SKILL BY USING FLIP PICTURE TECHNIQUE ON NARRATIVE TEXT TO THE NINTH GRADE STUDENTS AT SMP N 2 TABANAN - I Gede Gita Wiastra; I GEDE BAGUS WISNU BAYU TEMAJA; MAMINDA SUMIATI JOHAN; GUSTI AYU GEDE SUKRANINGSIH; I GUSTI BAGUS YOGA WIDIADNYA (FAKULTAS PENDIDIKAN BAHASA DAN SENI IKIP SARASWATI, 2025)
This study aims to improve the writing skills of ninth-grade students at SMP N 2 Tabanan through the application of the Flip Picture technique in narrative texts. This technique utilizes a series of images as visual aids to stimulate students' imagination and help them understand narrative structure. The research employed a classroom action research method with two main stages: pre-test and post-test. The findings revealed a significant improvement in students' writing abilities, with the average score increasing from 65 in the pre-test to 80 in the post-test. The Flip Picture technique proved effective in enhancing text organization, vocabulary usage, and student creativity. Additionally, students demonstrated higher motivation and engagement during the writing process. However, some students faced difficulties in constructing sentences due to limited vocabulary. This study concludes that the Flip Picture technique can serve as an innovative and interactive teaching method to enhance writing skills, particularly in narrative texts. Further research is recommended to combine this technique with vocabulary enhancement strategies for more comprehensive writing skill development.